Enhancement of CO2 adsorption and oxygen transfer properties on γ-Al2O3 support through surface modification with MgO-ZrO2 for coke suppression over Ni catalyst in CO2 reforming of methane - Sabaithip Tungkamani; Tanakorn Ratana; Supachai Jadsadajerm; Wassachol Sumarasingha; Monrudee Phongaksorn (Results in Engineering)
This work focuses on employing commercial γ-Al2O3 for surface modification with MgO-ZrO2 mixed oxide to enhance the potential of CO2 adsorption and oxygen mobility. This enhancement facilitates its application as a support in catalysts for CO2 utilization such as CO2 reforming of methane (CRM). To achieve this perspective, γ-Al2O3 was modified with 10 wt.% of various MgO and ZrO2 contents (MgO:ZrO2= 10:0, 9:1,7:3, 5:5, 3:7, 1:9 and 0:10) using the impregnation method. All samples including unmodified γ-Al2O3 (Al) were characterized. Due to the increase in basicity and oxygen transfer around the surface, the improvement of the CO2 adsorption was observed on γ-Al2O3 modified with 9 wt.% MgO-1 wt.% ZrO2 (9Mg1ZrAl) and 10 wt.% MgO (10MgAl), respectively. An application of these two superior samples as a support of 10 wt.% Ni (10Ni) catalysts for CRM was investigated and compared with an unmodified γ-Al2O3. Characterization results suggest the formation of NiO-MgO solid solution at the surface due to the decrease in metal-support interaction and the increase in metal dispersion. The Ni catalysts with the surface-modified support show higher CO2 activity that raises carbon deposition resistance. The greatest coke prevention was observed on 10Ni/9Mg1ZrAl that lowers the coke deposition by 42 % compared to 10Ni/Al. It indicates that the composition of this modification allowed very low ZrO2 portion to merge with MgO and MgO to form solid solution with NiO. This enables the 10Ni/9Mg1ZrAl catalyst to generate labile oxygens which can be conveyed to the Ni metal sites on the catalyst.